CONSTRUCTAL DESIGN OF A VORTEX TUBE FOR SEVERAL INLET STAGNATION PRESSURES - Marques, C. H.; Isoldi, L. A.; dos Santos, E. D.; Rocha, L. A. O. (Revista de Engenharia Térmica, 2012)
The present paper shows a numerical study concerned with the geometrical optimization of a vortex tube device by means of Constructal Design for several inlet stagnation pressures. In the present study, it is evaluated a vortex tube with two-dimensional axisymmetric computational domain with dry air as the working fluid. The compressible and turbulent flows are numerically solved with the commercial CFD package FLUENT, which is based on the Finite Volume Method. The turbulence is tackled with the k-ε model into the Reynolds Averaged Navier-Stokes (RANS) approach. The geometry has one global restriction, the total volume of the cylindrical tube, and four degrees of freedom: d3/D (the ratio between the diameter of the cold outlet and the diameter of the vortex tube), d1/D (the ratio between the diameter of the inlet nozzle and the diameter of the vortex tube), L2/L (the ratio between the length of the hot exit annulus and the length of the vortextube) and D/L (the ratio between the diameter of the vortex tube and its length). The degree of freedom L2/L will be represented here by the cold mass fraction (yc). In the present work it is optimized the degrees of freedom yc and d3/D while the other degrees of freedom and the global restriction are kept fixed. The purpose here is to maximize the amount of energy extracted from the cold region (cooling effect) for several geometries, as well as, investigate the influence of the inlet stagnation pressure over the optimal geometries. Results showed an increase of the twice maximized cooling heat transfer rate of nearly 330 % from 300 kPa to 700 kPa. Moreover, the optimization showed a higher dependence of (d3/D)o for the lower range of inlet pressures, while the optimization is more dependent of yc,oo for higher inlet stagnation pressures.